(untitled) (Research, Society and Development, 2025)
In the world, many people undergo rigorous treatments to lose weight. Surgery is currently considered the most effective and longest-lasting method of weight loss. This study aims to evaluate the percentage of weight loss in obese patients who underwent bariatric surgery between 2019 and 2023, in different periods after the surgical procedure. A longitudinal observational quantitative study was conducted to evaluate weight loss in 500 patients who underwent bariatric surgery (250 gastric bypasses and 250 vertical sleeve gastrectomy) from 2019 to 2023, with the surgery team, led by Dr. Guiherme Cotta, in different hospitals in the city of Rio de Janeiro (Hospital Copa D Or, Hospital Badim, Hospital Quinta D’Or, Hospital Marcos Moraes, Hospital Pasteur, Hospital Israelita Albert Sabim, Hospital Copa Star, Sao Jose Hospital, Gloria D’Or Hospital, Amparo Hospital). Weight loss was analyzed in four periods after surgery (one month, three months, six months, and twelve months). Mean weight loss percentages were compared to using SPSS version 27. The results showed that the body weight, and BMI decrease, are plausible from the same first month for both procedures. Sleeve gastrectomy produces rapid weight loss from the first month (12.06%), but gastric bypass shows better results after one year of bariatric surgery (34.88% for 33.03% of sleeve gastrectomy), although without significant differences.